The Book of Mormon: A Very Short Introduction - Givens, Terryl L. (New York Oxford University Press, 2009)
Givens examines the Book of Mormon first and foremost in terms of the claims that its narrators make for its historical genesis, its purpose as a sacred text, and its meaning for an audience which shifts over the course of the history it unfolds. The author traces five governing themes in particular--revelation, Christ, Zion, scripture, and covenant--and analyzes the Book's central doctrines and teachings. Some of these resonate with familiar nineteenth-century religious preoccupations; others consist of radical and unexpected takes on topics from the fall of Man to Christ's mortal ministries and the meaning of atonement. Givens also provides samples of a cast of characters that number in the hundreds, and analyzes representative passages from a work that encompasses tragedy, poetry, sermons, visions, family histories and military chronicles. Finally, this introduction surveys the contested origins and production of a work held by millions to be scripture, and reviews the scholarly debates that address questions of the record's historicity.
Includes Index and Illustrations.
Keywords: Book of Mormon -- Introduction